1994
DOI: 10.1063/1.112830
|View full text |Cite
|
Sign up to set email alerts
|

High current YBa2Cu3O7−δ thick films on flexible nickel substrates with textured buffer layers

Abstract: High current YBa2Cu3O7−δ (YBCO) thick films on flexible nickel substrates with textured buffer layers were fabricated. Highly textured yttria-stabilized-zirconia buffer layers were deposited by using ion beam assisted deposition (IBAD). Pulsed laser deposited YBCO films were not only c-axis oriented with respect to the film surface but also strongly in-plane textured. The in-plane mosaic spread of YBCO films was ∼10°. A critical current density of 8×105 A/cm2 was obtained at 75 K and zero field for thin YBCO f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(49 citation statements)
references
References 12 publications
(12 reference statements)
1
46
1
Order By: Relevance
“…In order to control the inplane alignment of polycrystalline YBCO films, several techniques have been developed. Biaxially-aligned yttriastabilized zirconia (YSZ) buf€ier layers have been grown on polycrystalline Ni-based alloy tapes by ion-beam-assisted deposition (IBAD) [3], [4] We successfilly deposited biaxially-aligned Y~0 3 buffer layers on cube-textured Ni substrates by electron bean deposition. This technique easily produces the: YzO~ buffer layers, needing only control of the deposition pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In order to control the inplane alignment of polycrystalline YBCO films, several techniques have been developed. Biaxially-aligned yttriastabilized zirconia (YSZ) buf€ier layers have been grown on polycrystalline Ni-based alloy tapes by ion-beam-assisted deposition (IBAD) [3], [4] We successfilly deposited biaxially-aligned Y~0 3 buffer layers on cube-textured Ni substrates by electron bean deposition. This technique easily produces the: YzO~ buffer layers, needing only control of the deposition pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The value of the critical transport current of a superconductor was shown to depend on the perfection degree of its crystallographic texture, which, in turn, is controlled by the perfection degree of the cube texture of the nickel substrate (Wu et al, 1994;Goyal et al, 1996;*Corresponding author. Fax: (3432) 74 5244, e-mail: sokolov@imp.uran.ru Norton et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These applications, however, rely on the availability of high quality films on metallic substrates with high transport critical currents at 77 K. Recently, it has been shown that by depositing a YSZ buffer layer using an obliquely impinging ion-beam assisted deposition (IBAD) process, high J c YBCO thin films can be grown on polycrystalline metallic substrates (Iijima et al 1992;Reade et al 1992;Sonnenberg et al 1993;Wu et al 1994). The J c increase for these films is due to a biaxially aligned YSZ buffer layer produced by the IBAD process, resulting in a reduction of the weak links at high-angle grain boundaries in the subsequently grown YBCO films.…”
Section: Introductionmentioning
confidence: 99%